2020
DOI: 10.22201/fmvz.24486760e.2020.2.562
|View full text |Cite
|
Sign up to set email alerts
|

Production response in dairy cows milked two or three times a day: A meta-analysis

Abstract: The objective was to evaluate the effects of two (2×) vs three (3×) times per day milking on milk production and milk composition in dairy cows. Fourteen scientific papers, containing production data from 16 trials, where dairy cows were milked 2× or 3×, were analysed using meta-analysis with fixed and random-effects with the R statistical program. The degree of heterogeneity and publication bias were measured with the I2 statistic and Begg’s test, respectively. In addition, the meta-regression analysis explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…MF showed a significant effect on MY, and ECM and no effect on % fat, protein, or lactose. These results agree with the previously reported results that milking 3X leads to an increase in MY with little or no change in milk content [32]. There are several mechanisms that explain the increased MY, such as the increase in the number of mammary epithelial cells, their decreased apoptosis, increased cell activity, and the absence of lactation inhibitors [33].…”
Section: Milking Frequency and Energy Balance Adaptationsupporting
confidence: 93%
“…MF showed a significant effect on MY, and ECM and no effect on % fat, protein, or lactose. These results agree with the previously reported results that milking 3X leads to an increase in MY with little or no change in milk content [32]. There are several mechanisms that explain the increased MY, such as the increase in the number of mammary epithelial cells, their decreased apoptosis, increased cell activity, and the absence of lactation inhibitors [33].…”
Section: Milking Frequency and Energy Balance Adaptationsupporting
confidence: 93%
“…Milk production increases with age [49]. Consequently, the milk production of a dairy cow will increase according to its number of lactations, leading to an increase in the number of working days from the initial 275 days to 305 days, which is an optimal scenario.…”
Section: The Project Expenses For the Three Business Modelsmentioning
confidence: 99%
“…The authors identified some risk factors; increased parity, later stage of lactation, not milking clinical and subclinical cases last, lack of routine cleaning of the milking parlour, using the dry-off treatment and optimized feed before calving. According to Sánchez-Duarte et al (2020), increasing milking frequency from twice to three times per day positively affects milk production and yields of milk fat and milk protein without increasing dry matter intake. Application of three times per day milking frequency must consider dairy cow management, labour availability, and milking parlour infrastructure particular to each dairy farm.…”
Section: Introductionmentioning
confidence: 99%